LWT-PWN - Borin, Lars (University of Gothenburg, 2024)
LWT-PWN is the IDS/LWT concept list linked to Princeton WordNet 3.0 word sense identifiers.

LWT-PWN är IDS/LWT-begreppslistan med länkar till ordbetydelseidentifierare i Princeton WordNet 3.0.
LWT-PWN
Keywords: Language Technology (Computational Linguistics); lexicon; Natural Language Processing; Språkbehandling och datorlingvistik